Abdominal cerclage in a patient with a neocervix with planned cesarean hysterectomy at delivery. Issue 1 (20th October 2020) - Schaible, Burk; Haught, Erica; Vozar, Amber; Riggs, Kassandra; Calhoun, Byron; Bush, Stephen; Bush, Stephen
Abstract: Pregnancies complicated by congenital uterine anomalies (CUA) with a neocervix present a variety of challenges for the obstetrician. Abdominal cerclage can be utilized to help prevent preterm delivery in a patient with a neocervix. A 14‐year‐old female presented with right adnexal pain and was found to have a complex uterine anomaly resembling a noncommunicating unicornuate uterus with a cervix embedded in the rudimentary horn. A neocervix was created during surgical removal of the rudimentary horn. The patient became pregnant at age 24, and a transabdominal cerclage served an important role in the prevention of preterm delivery. Although limited data exists regarding the outcomes for the use of abdominal cerclage after the creation of a neocervix, term delivery is possible with said intervention.